A dominant negative form of Rac1 affects myogenesis of adult thoracic muscles in Drosophila. - Fernandes, J.J.; Atreya, K.B.; Desai, K.M.; Hall, R.E.; Patel, M.D.; Desai, A.A.; Benham, A.E.; Mable, J.L.; Straessle, J.L. (Developmental Biology, 2005)
Blocking Rac1 function in precursors of the indirect flight muscle of Drosophila severely disrupts muscle formation. The DLM fibers that develop using larval scaffolds are reduced in number and fiber size, while the DVMs, which develop using founder cells, are mostly absent. These adult muscle phenotypes are in part due to a reduced myoblast pool present at the third larval instar. BrDU labeling studies indicated that this is primarily due to a reduction in proliferation. In addition, DVM myoblasts display altered morphology and are unable to segregate into primordia. This defect precedes the evident block in fusion. We also show that the recently described DVM founder cells can be labeled with 22C10 and beta-3 tubulin, and that they are present under conditions of dominant negative Rac1(N17) expression. Despite the presence of founder cells, DVM fiber formation is rarely observed. Although DLM myoblasts are able to segregate around their larval scaffolds, the pace of fusion is reduced and consequently there is a delay in DLM fiber formation. Thus, in addition to its well-established role in fusion, Rac1 is also involved in the regulation of myoblast proliferation and segregation during adult myogenesis. These are two new roles for Rac1 in Drosophila.